2004
DOI: 10.1104/pp.103.031765
|View full text |Cite
|
Sign up to set email alerts
|

Condensed Lignins Are Synthesized in Poplar Leaves Exposed to Ozone

Abstract: Poplar (Populus tremula ϫ alba) trees (clone INRA 717-1-B4) were cultivated for 1 month in phytotronic chambers with two different levels of ozone (60 and 120 nL L Ϫ1 ). Foliar activities of shikimate dehydrogenase (EC 1.1.1.25), phenylalanine ammonia lyase (EC 4.3.1.5), and cinnamyl alcohol dehydrogenase (CAD, EC 1.1.1.195) were compared with control levels. In addition, we examined lignin content and structure in control and ozone-fumigated leaves. Under ozone exposure, CAD activity and CAD RNA levels were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
96
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 123 publications
(108 citation statements)
references
References 58 publications
7
96
1
2
Order By: Relevance
“…By contrast, the silencing of LAC4 or LAC17 had no effect on the frequency of condensed bonds in stem lignins, except for the semidwarf lac4-2 lac17 samples (thioacidolysis yield 25% lower than the control level when calculated in mmoles per gram of lignin). This result provides further support for the hypothesis that the semidwarf phenotype of lac4-2 lac17 is induced by stress, as lignins formed in response to stress are enriched in condensed bonds (Cabané et al, 2004;Betz et al, 2009).…”
Section: Disruption Of Lac4 And/or Lac17 Affects Plant Development Vsupporting
confidence: 75%
“…By contrast, the silencing of LAC4 or LAC17 had no effect on the frequency of condensed bonds in stem lignins, except for the semidwarf lac4-2 lac17 samples (thioacidolysis yield 25% lower than the control level when calculated in mmoles per gram of lignin). This result provides further support for the hypothesis that the semidwarf phenotype of lac4-2 lac17 is induced by stress, as lignins formed in response to stress are enriched in condensed bonds (Cabané et al, 2004;Betz et al, 2009).…”
Section: Disruption Of Lac4 And/or Lac17 Affects Plant Development Vsupporting
confidence: 75%
“…O 3 increased both enzyme activities and related gene transcript levels involved in lignin biosynthesis in Pinus sylvestris (Rosemann and Heller 1991;Zinser et al 1998), Picea abies (Galliano et al 1993a;Galliano et al 1993b;Heller et al 1990), Populus spp. (Cabané et al 2004;Di Baccio et al 2008;Koch et al 1998;Wustman et al 2001), Betula pendula (Pääkkönen et al 1998a;Tuomainen et al 1996) and Fagus sylvatica (Jehnes et al 2007;Olbrich et al 2005). The responses of the phenylpropanoid metabolism can be both fast (Koch et al 1998) and substantial (Cabané et al 2004), and the induction levels were generally correlated with O 3 concentrations (Cabané et al 2004;Galliano et al 1993b;Rosemann et al 1991).…”
Section: Cell Wall Component Biosynthesis In Leaves and Stemsmentioning
confidence: 99%
“…ARA, a glycosyl hydrolase, also is connected with secondary cell wall formation and cell wall reorganization (Sumiyoshi et al, 2013). Generally, poplar leaves respond to ozone stress with an up-regulation of gene expression and enzyme activities of phenylpropanoid and lignin biosynthetic proteins (Richet et al, 2012), which lead to higher contents of condensed lignin, hydroxycinnamic acids, and flavonoids (Booker and Miller, 1998;Cabané et al, 2004). We recently described the denitrosylation of PAL and COMT in wild-type gray poplar upon ozone exposure and demonstrated for PAL that in vitro PAL activity increased as a result of denitrosylation.…”
Section: Target Sites Of No Action In Ie and Ne Gray Poplarmentioning
confidence: 99%
“…We recently described the denitrosylation of PAL and COMT in wild-type gray poplar upon ozone exposure and demonstrated for PAL that in vitro PAL activity increased as a result of denitrosylation. Because PAL is a key regulatory enzyme controlling the metabolic flux in the phenylpropanoid and downstream biosynthetic pathways (Booker and Miller, 1998;Cabané et al, 2004), the activities of the other enzymes of the phenolic secondary metabolism, such as COMT and CAD, also may be rapidly regulated by S-nitrosylation. In the NE genotype but not the IE genotype, the CAD protein, catalyzing the final step in the synthesis of monolignols (Di Baccio et al, 2008), was found to be S-nitrosylated after ozone exposure (Table I).…”
Section: Target Sites Of No Action In Ie and Ne Gray Poplarmentioning
confidence: 99%